2023
DOI: 10.1186/s41043-023-00370-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between academic performance indicators and lifestyle behaviors among Kuwaiti college students

Abstract: Background Lifestyle behaviors are developed during young adulthood and carried through life. Accordingly, early detection of unhealthy behaviors can help prevent the increase in non-communicable diseases in the population. College students are an especially vulnerable group who, upon entering a new environment, tend to engage in unhealthy behaviors. Objective The present study aims to evaluate the lifestyle behaviors of Kuwaiti college students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Eating habits have a significant impact on academic performance. As many studies have shown, students who have regular nutritious meals tend to have better concentration, memory, and academic performance than those with poor eating habits such as skipping meals and consuming high amounts of fast food [ 16 - 19 ]. This is in line with the current study's results, which found that students who often or always have breakfast are less likely to experience low academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Eating habits have a significant impact on academic performance. As many studies have shown, students who have regular nutritious meals tend to have better concentration, memory, and academic performance than those with poor eating habits such as skipping meals and consuming high amounts of fast food [ 16 - 19 ]. This is in line with the current study's results, which found that students who often or always have breakfast are less likely to experience low academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, males had greater waist circumferences and body weights but not greater BMIs. Interestingly, few studies have reported similar rates of obesity/overweight among students upon admission to university (51,52). However, additional quality longitudinal studies are needed to determine the determinants of changes in behavior across these life transitions, which are associated with deterioration of lifestyle behaviors and gains in adiposity as individuals enter adulthood (11).…”
Section: Discussionmentioning
confidence: 99%
“…This enabled us to assess changes in BMI and body weight during the pandemic period. The current data used in the present study were part of a prior research project [26].…”
Section: Questionnaire and Data Collectionmentioning
confidence: 99%